Revision of the Holarctic genus Gloma Meigen (Diptera: Empidoidea: Brachystomatidae: Trichopezinae) - Sinclair, Bradley J.; Cumming, Jeffrey M.; Brooks, Scott E.; Saigusa, Toyohei (Zootaxa, 2019)
The Holarctic genus Gloma Meigen is revised and includes five species (G. fuscipennis Meigen, G. fuscipes Melander, G. luctuosa Melander, G. pectinipes Melander, G. pyricornis Saigusa & Sinclair sp. nov.) and two undescribed species from China, presently known only from females. The monotypic Baltic amber genus Palaeoparamesia Meunier is discussed as possibly congeneric with Gloma. The Baltic amber species Gloma hirta Loew is considered a nomen dubium. A lectotype is designated for Gloma luctuosa. All species are described or diagnosed, and their geographic distributions mapped. A World key to the species of Gloma is provided. Phylogenetic placement of the genus, including a possible new relationship with Oreogeton Schiner is considered, and the relationships and zoogeographic history of the species are discussed based on a morphological cladistic analysis.